Does the PCAOB international inspection program improve audit quality for non-US-listed foreign clients? - Fung, Simon Yu Kit; Raman, K.K.; Zhu, Xindong (Kevin) (Journal of Accounting and Economics, 2017)
We examine whether the Public Company Accounting Oversight Board (PCAOB) international inspection program improves audit quality for a sample of non-US-listed foreign public client companies from 55 countries audited by foreign (i.e., non-US) auditors. For a sample of non-US-listed clients of PCAOB-registered foreign auditors, we find that initial PCAOB inspections improve audit quality, over and above the threat of such inspections, for foreign auditors’ non-US-listed foreign clients. Our findings document the benefits of PCAOB international inspections for foreign investors in non-US-listed foreign companies which could increase the acceptability of the PCAOB international inspection program abroad.